Ethnobotanical investigation on medicinal plants used by local populations in Tlemcen National Park (extreme North West Algeria) - Zatout, Fayza; Benarba, Bachir; Bouazza, Asmaa; Babali, Brahim; Nacer Bey, Nazli; Morsli, Abdelkader (Mediterranean Botany, 2021)
Medicinal plants are currently used by local populations to treat different diseases around the world. In the present study, the local knowledge of medicinal plants used by indigenous populations living in the Park of Tlemcen (North-West Algeria) has been documented. A total of 254 informants with a strong ethnomedicinal knowledge living in the national park of Tlemcen were interviewed by using a questionnaire. Data collected was analyzed using quantitative indices such as the ethnobotanicity index (EI), use value (UV), and Informant Consensus Factor (FIC). 109 species belonging to 54 families were identified and used by indigenous populations to treat different diseases. The most frequent families were lamiaceae (15.5%), asteraceae (11.9%), and rosaceae (5.5%). Roots, rhizomes or tubers were the most used part for medical care (37.6%), followed by leaves (33.6%), other aerial parts (16%), fruits (8%), flowers (1.6%), and seeds (3.2%). Regarding modes of preparation, we noticed that decoction (40.4%) and infusion (28.5%) were the most predominant. Moreover, Thymus lanceolatus (UV=0.96), Origon glandulosum (UV=0.96) and Ammoides verticillata (UV=0.94) were the most frequently used species. FIC values ranged from 0.65 to 0.98. The highest FIC were recorded for reproductive and sexual disorders (0.98), respiratory tract diseases (0.98), cardiovascular system disease and blood disorders (0.94), digestive disorders (0.93), and general health (0.93). A variety of species are used to treat several ailments. Recorded species with high UV should be prioritized for conservation and subjected to further phytochemical and pharmacological studies.